2022
DOI: 10.4103/1673-5374.336870
|View full text |Cite
|
Sign up to set email alerts
|

Role of adipose tissue grafting and adipose-derived stem cells in peripheral nerve surgery

Abstract: The application of autologous fat grafting in reconstructive surgery is commonly used to improve functional form. This review aims to provide an overview of the scientific evidence on the biology of adipose tissue, the role of adipose-derived stem cells, and the indications of adipose tissue grafting in peripheral nerve surgery. Adipose tissue is easily accessible through the lower abdomen and inner thighs. Non-vascularized adipose tissue grafting does not support oxidative and ischemic stress, resulting in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 120 publications
1
15
0
Order By: Relevance
“…When appropriately stimulated by the microenvironment, stem cells can influence vascularity via cell‐to‐cell communications, differentiation, and release of VEGF, making them ideal for vascularization of tissue‐engineered constructs (Hong et al, 2010; Rehman et al, 2004). Of the various MSCs, adipose‐derived mesenchymal stem cells (ADSCs) have been extensively studied for enhancement of nerve graft vascularization, due to its ease of harvest (via minimally invasive techniques such as liposuction), superior stem cell fraction, pluripotency, and ease of in vitro expansion and proliferation (Saffari et al, 2022). ADSCs facilitate angiogenesis directly by differentiating into vascular endothelium and indirectly via endogenous SC expression of growth factors such as nerve growth factor (NGF), brain‐derived neurotrophic factor (BDNF), and VEGF (Erba et al, 2010; Rhode et al, 2021).…”
Section: Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…When appropriately stimulated by the microenvironment, stem cells can influence vascularity via cell‐to‐cell communications, differentiation, and release of VEGF, making them ideal for vascularization of tissue‐engineered constructs (Hong et al, 2010; Rehman et al, 2004). Of the various MSCs, adipose‐derived mesenchymal stem cells (ADSCs) have been extensively studied for enhancement of nerve graft vascularization, due to its ease of harvest (via minimally invasive techniques such as liposuction), superior stem cell fraction, pluripotency, and ease of in vitro expansion and proliferation (Saffari et al, 2022). ADSCs facilitate angiogenesis directly by differentiating into vascular endothelium and indirectly via endogenous SC expression of growth factors such as nerve growth factor (NGF), brain‐derived neurotrophic factor (BDNF), and VEGF (Erba et al, 2010; Rhode et al, 2021).…”
Section: Stem Cellsmentioning
confidence: 99%
“…ADSCs facilitate angiogenesis directly by differentiating into vascular endothelium and indirectly via endogenous SC expression of growth factors such as nerve growth factor (NGF), brain‐derived neurotrophic factor (BDNF), and VEGF (Erba et al, 2010; Rhode et al, 2021). ADSCs can also regulate the ECM to promote tissue regeneration and scar tissue reduction (Dong et al, 2020; Saffari et al, 2022). An in vitro study demonstrated that ADSCs seeded onto ANA increased mRNA and protein expression of neurotrophic and angiogenic factors, such as BDNF and VEGFa (Rbia et al, 2019).…”
Section: Stem Cellsmentioning
confidence: 99%
“…It is important to assess the revascularization and regeneration of decellularized tumor-bearing nerve grafts treated with liquid nitrogen [1-3, 5, 6, 9]. The local cell population—for example, the number of Schwann cells, fibroblasts, intraneural fibrosis, and vascularity density—is important in order to evaluate regeneration capabilities.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The local cell population-for example, the number of Schwann cells, fibroblasts, intraneural fibrosis, and vascularity density-is important in order to evaluate regeneration capabilities. Adipose-derived stem cells, vascular endothelial growth factor, or fat tissue composite grafts have been reported to promote regeneration of nerve grafts [1,2,5,6]. Finally, longerterm observation of nerve grafts would provide data about integrity maintenance, functional outcomes, and late sequelae such as neuroma, neuropathic pain, and paresthesia [3,7,9].…”
mentioning
confidence: 99%
“…Autologous fat grafting is one of the most effective and safest technique in reconstructive surgery to promote functional and esthetic form [ 1 ]. It has several advantages such as accessibility to adipose tissue, inexpensive, non-immunogenicity and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%